2017
DOI: 10.1371/journal.pone.0176053
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional changes in litchi (Litchi chinensis Sonn.) inflorescences treated with uniconazole

Abstract: In Arabidopsis, treating shoots with uniconazole can result in enhanced primary root elongation and bolting delay. Uniconazole spraying has become an important cultivation technique in controlling the flowering and improving the fruit-setting of litchi. However, the mechanism by which uniconazole regulates the complicated developmental processes in litchi remains unclear. This study aimed to determine which signal pathways and genes drive the responses of litchi inflorescences to uniconazole treatment. We moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Uniconazole treatment of litchi inflorescences can control flowering and improve fruit-setting in litchi [ 29 ]. LcCCD4 , LcCCD4c2 , LcCCD8a , LcNCED2, and LcNCED3 showed down-regulated expression obviously in the entire inflorescences after uniconazole spraying, decreased by 1.72, 1.53, 15.97, 2.80, and 3.18 times separately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uniconazole treatment of litchi inflorescences can control flowering and improve fruit-setting in litchi [ 29 ]. LcCCD4 , LcCCD4c2 , LcCCD8a , LcNCED2, and LcNCED3 showed down-regulated expression obviously in the entire inflorescences after uniconazole spraying, decreased by 1.72, 1.53, 15.97, 2.80, and 3.18 times separately.…”
Section: Resultsmentioning
confidence: 99%
“…(3) Three stages of peel samples of ‘Nuomici’ litchi: green, yellow and red peel stage, accession number is SRP047115 ( https://www.ncbi.nlm.nih.gov/sra/?term=SRP047115 ) [ 28 ]. (4) The entire inflorescences samples on 28 days after the uniconazole treatment, accession number is SRP092890 ( https://www.ncbi.nlm.nih.gov/sra/?term=SRP092890 ) [ 29 ]. (5) The fruit samples on 2d, 4d and 7d after fruit abscission of ‘Wuye’ litchi caused by girdling plus defoliation treatment (GPD), accession number is SRA234477 ( https://www.ncbi.nlm.nih.gov/sra/?term=SRA234477 ) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the phylogenetic relationship analysis ( Figure 3 ), LcMADS95 ( LcAP1 ), LcMADS75 ( LcAP3-1 ), LcMADS45 ( LcAP3-2 ), LcMADS50 ( LcPI ), LcMADS65 ( LcAG ), LcMADS51 ( LcSTK ), LcMADS11 ( LcSHP ), LcMADS100 ( LcSEP1 ), LcMADS94 ( LcSEP2 ), LcMADS91 ( LcSEP3 ), and LcMADS73 ( LcSEP4 ) represented ABCDE genes. A previous study observed the regulation of GA and its inhibitor (uniconazole) in litchi sex determination [ 17 ], and JA has shown an antagonistic role to GA in flower development [ 18 ]. Hence, we tested the response of genes involved in the ABCDE model to these two hormones in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Uniconazole is a member of the triazole family that is known to bind to the active sites of cytochrome P450 enzymes by both coordinating to the heme-iron atom and interacting with neighboring amino acid residues ( Saito et al, 2006 ). Despite the fact that it has the side effect of inhibiting the biosynthesis of gibberellic acid (GA) and brassinosteroid (BR) ( Min et al, 1999 ), uniconazole can protect plants from various stresses, in addition to various other functions, such as enhancing the levels of carotenoid and chlorophyll ( Fletcher and Hofstra, 1990 ), promoting the accumulation of starch ( Liu et al, 2015 ), improving primary root elongation and delay bolting in Arabidopsis , controlling the flowering, enhancing fruit setting ( Wei et al, 2017 ), elevating yield components in crop plants ( Zhou and Ye, 1996 ; Ahmad et al, 2018 ), and changing the content of endogenous hormones ( Zhang et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%